The effect of elexacaftor/tezacaftor/ivacaftor on non-pulmonary symptoms in adults with cystic fibrosis - Sarah Allgood; Reena Levy; Despina Bubaris; Kristin Riekert; Kevin J. Psoter; Noah Lechtzin (Heliyon, 2023)
Background: Elexacaftor/Tezacaftor/Ivacaftor (ETI) is a CFTR modulator that has led to large benefits in lung function, pulmonary exacerbation rates, and respiratory symptoms. Less is known about the effect of ETI on non-pulmonary symptoms. The objective of this study was to examine the changes in patient reported outcomes after starting ETI in multiple non-pulmonary symptoms. Methods: This was a prospective cohort study of adults with CF. Participants completed questionnaires prior to starting ETI and then at weeks 2, 4, 6, 8, 10, 12, and 14 after starting ETI. They completed the following validated instruments: PROMIS Pain Intensity, PROMIS Pain Interference, FACIT Fatigue, SNOT22, PAC-SYM, PHQ8, GAD7 and Pittsburgh Sleep Quality Index. Longitudinal changes for outcomes were modelled using linear regression based on general estimating equations. Results: 22 participants enrolled who answered questionnaires before and after starting ETI. The median age was 35.3 years (IQR 11.1) and 13 (59.1%) were male. In models adjusted for age, sex, and baseline value there were significant improvements in pain interference (β = −2.57; 95% CI -4.92, −0.23), sinus symptoms (β = −4.50; 95% CI -7.59, −1.41), and sleep disturbance (β = −1.90; 95% CI -2.71, −1.09) over 14 weeks after starting ETI. No symptom areas worsened over the study period. Conclusions: In this prospective study we found statistically significant improvements in three different non-pulmonary symptom areas in people with CF started on ETI. While this was a small, uncontrolled study it suggests that use of highly effective CFTR modulators can result in benefits for patients beyond pulmonary symptoms.